`PROFIL TINEA KAPITIS DI POLIKLINIK KULIT DAN KELAMIN RSUD DR. PIRNGADI KOTA MEDAN PERIODE 2014 - 2017 - NAHDA RIZKINA; FEBRINA DEWI PRATIWI LINGGA (JURNAL ILMIAH SIMANTEK, 2020)
The World Health Organization (WHO) claimed that tinea capitis was the second most common infantile infection afterpyoderm and until now there are still a few tinea capitis studies in Medan. Previous research in H. Adam Malik Hospital in2009- 2014 obtained most patients were 11-15 years old (43,8%), kerion (40,6%), and the most caused of tinea capitis wasMicrosporum (75%). Based on the introduction, researcher wanted to further examine the profile of tinea capitis in one of thehospitals in Medan. To determine the profile of tinea capitis at the Outpatient Clinic of Dermatology and Venerology in Dr.Pirngadi in Medan in the period of 2014-2017. Descriptive study with cross sectional research design with a retrospectiveapproach from secondary data on patients treated at the Outpatient Clinic of Dermatology and Venerology in Dr. Pirngadi inMedan in the period of 2014-2017. The results of this study were 18 patients with tinea capitis. The onset of age was 0 yearsto over 65 years, the highest percentage (27.8%) was at the age group 5-11 years. The incidence of tinea capitis was morefrequently occurred on women (61,1%) than men (38,9%). Most patients lived in Medan (77,52%). The chief complaint wasscaly scalp (55,6%). The most interval of age was in children (5-11 years old), women is more frequent than men, the mostresidence is in Medan and the chief complaint is scaly scalp.